An Assessment of the Impact of ISNAR: 1997-2001 - Anderson, Jock R.; Ponniah Anandajayasekeram; Eric Craswell; Mandivamba Rukuni (International Service for National Agricultural Research, 2004)
In preparation for its fourth External Program and Management Review (EPMR), the International Service for National Agricultural Research (ISNAR) commissioned a team to report on ISNAR's achievements, impacts and constraints in the period from 1997 to 2001. The report was to include an assessment of ISNAR outputs (including publications, training manuals, reports, planning documents, etc.), an evaluation of changes in the capacity and performance of agricultural research organizations that could be linked to ISNAR's activities, an assessment of the degree to which such changes could be related to the ultimate goals of the Consultative Group on International Agricultural Research (CGIAR), together with recommendations for increasing the impact of ISNAR's work. The report, submitted in July 2002, was originally targeted at those conducting the EPMR, together with ISNAR management and staff. It was subsequently felt that the report should be made available to a wider readership, including those in the CGIAR system in general (particularly donors and investors), managers of national agricultural research institutes (NARIs) and others active in agricultural research at national and regional levels. Most of the work involved in preparing the report was conducted between April and the end of June 2002. Given the limited time available, a framework was needed to guide the team's efforts. Several methods were used, including surveys of various partners (e.g. a global attitude survey of employees of national agricultural research systems (NARSs) (N=315), NARI managers (N=246), direct collaborators (N=135), donors (associated with specific projects) (N=22), advanced research institutes (ARIs) and international agricultural research centers (IARCs) (N=43), subregional organizations (SROs) (N=8), trainees and their supervisors (N=310), those who downloaded computer-based ISNAR training modules (N=30), and ISNAR publication users (N=500). These surveys were complemented by 11 case studies of different countries in which ISNAR had conducted collaborative work (Argentina, Cuba, Dominican Republic, Indonesia, Mexico, Pakistan, South Africa, Sri Lanka, Uganda, Vietnam, and Zambia). In its review of these and of ISNAR's own materials, the assessment team paid particular attention to evidence of the following: institutional development, developmental impact in general, raising awareness among clients, direct contributions to knowledge and indirect contributions to knowledge through influencing policy. In addition, various focal projects were examined separately, including the ISNAR Biotechnology Service (IBS) and the project on Agricultural Science and Technology Indicators (ASTI). The latter has informed debate both at national and subregional levels (e.g. on the declining support for agricultural research, setting research priorities, etc.), while the former has assisted the development of biotechnology and biosafety policies in a number of countries, including Argentina, Cameroon, Chile, China, Egypt, Indonesia, Kenya, Malaysia, Mexico, Namibia, Nigeria, Philippines, Turkey, Uganda, and Zimbabwe.